The Influence of Product Quality, Brand Image, and Word-of-Mouth Recommendations on Purchasing Decisions - Putu Ines Solatika; Meydy Fauziridwan; Arini Hidayah; Totok Haryanto (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of product quality, brand image, and word-of-mouth recommendations on the decision to purchase Wardah cosmetics in Purwokerto. This study involved 120 students from Muhammadiyah University Purwokerto, Jenderal Soedirman University, and UIN Saizu Purwokerto who had used Wardah cosmetics, using a purposive sampling method. Data analysis was performed using Structural Equation Modeling (SEM) with the help of SmartPLS version 3.0 through external and internal model evaluation. The validity (AVE > 0.5) and reliability (Composite Reliability > 0.7) test results showed that all instruments were valid and reliable. The research results were tested based on the path coefficient value and P value (< 0.05). The results show that product quality, brand image, and word of mouth recommendations have a positive and significant effect on the decision to purchase Wardah cosmetics in Purwokerto. The contribution of this study lies in the integration of the word of mouth variable into the cosmetic purchase decision model, thereby providing a more comprehensive understanding of the role of consumer-to-consumer communication in influencing purchase decisions, particularly for local cosmetic products among students.